2017
DOI: 10.12659/msm.906179
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Exercise Acutely Increases Substantia Nigra and Prefrontal Brain Activity in Parkinson’s Disease

Abstract: BackgroundPathologic alterations in resting-state brain activity patterns exist among individuals with Parkinson’s disease (PD). Since physical exercise alters resting-state brain activity in non-PD populations and improves PD symptoms, we assessed the acute effect of exercise on resting-state brain activity in exercise-trained individuals with PD.Material/MethodsResting-state functional magnetic resonance imaging (fMRI) was collected twice for 17 PD participants at the conclusion of an exercise intervention. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 41 publications
(54 reference statements)
2
26
0
2
Order By: Relevance
“…Long-lasting aerobic activity and resistance exercise have been shown to induce an increase of circulating factors such as IGF-1, BDNF and NGF, which may affect brain plasticity in physiological aging or neurodegenerative pathologies. In neurological disorders, exercise training can provide participants with specific clinical benefits, but only if repeated habitually over a period of time [40].…”
Section: Discussionmentioning
confidence: 99%
“…Long-lasting aerobic activity and resistance exercise have been shown to induce an increase of circulating factors such as IGF-1, BDNF and NGF, which may affect brain plasticity in physiological aging or neurodegenerative pathologies. In neurological disorders, exercise training can provide participants with specific clinical benefits, but only if repeated habitually over a period of time [40].…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory has demonstrated that 16 weeks of highintensity resistance exercise rehabilitation training (RT) not only restores skeletal muscle mass and strength to levels found in healthy adults but also leads to improvements in cognition, well-being, and both overall and motor-specific domains of the Unified Parkinson's Disease Rating Score (UPDRS) and 39-item Parkinson's Disease Questionnaire (PDQ-39), validated metrics of PD severity (Kelly et al, 2014). Furthermore, fMRI analysis performed immediately after a single acute bout of this RT regimen demonstrates heightened activity in key brain regions, including the substantia nigra and prefrontal cortex (Kelly et al, 2017). If these acute effects are predictive of motor and cognitive adaptations to training (Voss et al, 2019) this may provide a mechanistic link to improvements in both motor and non-motor symptoms of PD seen following 16-week RT.…”
Section: Introductionmentioning
confidence: 89%
“…Moreover, and although not mutually independent of the hemo-neural hypothesis, exercise has been shown to alter coherent neural activity associated with resting state functional connectivity. Schmitt et al (2019) reported that a single bout of light intensity (i.e., <35% of lactate threshold) aerobic exercise improved resting state functional connectivity across frontoparietal networks (see also Kelly et al, 2017). Given that task demands for the SD and MD saccades used here require response mediation via a PFC mechanism (see above) and attentional-mediated visuo-motor transformations via parietal circuitry (Zhang and Barash, 2000), it is reasonable to assert that the diminished switch-cost is, in part, linked to improved resting state connectivity within frontoparietal networks.…”
Section: Experiments 1 and 2: A Post-exercise Reduction In The Unidirmentioning
confidence: 99%
“…Chang et al (2014) reported a 22 ms reduction in Stroop interference response times from pre-to post-exercise. Chang et al (2014) and Li et al (2014) attributed their findings to an exercise-based improvement in working memory and inhibitory control, respectively, with such benefits linked to: (1) increased catecholamine (Zouhal et al, 2008) and brain-derived neurotrophic factor (Knaepen et al, 2010) concentration and (2) blood flow related temperature and mechanical changes to the brain's neural and glial networks that improve neural efficiency (i.e., the hemo-neural hypothesis) (Moore and Cao, 2008) and functional connectivity (Kelly et al, 2017).…”
Section: Introductionmentioning
confidence: 99%